Impact of parent-related factors on dental caries in the permanent dentition of 6–12-year-old children: A systematic review. (March 2016) - Kumar, Santhosh; Tadakamadla, Jyothi; Kroon, Jeroen; Johnson, Newell W.
Abstract: Objective: To synthesise data from the literature on the effects of various parent-related characteristics (socio-demographic, behavioural and family environment) on dental caries in the permanent dentition of children. Data: Available studies in which the effects of parent-related characteristics on dental caries experience in the permanent dentition of children aged 6–12 years were evaluated. Sources: PubMed, Medline via OVID and CINAHL Plus via EBSCO, restricted to scientific articles, were searched in April 2015. English language and time filters (articles published from 2000) were used. Study selection: A total of 4162 titles were retrieved, of which 2578 remained after duplicates were removed. After review of titles and their abstracts by two independent reviewers, 114 articles were considered relevant for full text review. Of these, 48 were considered for final inclusion. Data extraction was performed by two authors using piloted data extraction sheets. Conclusions: Most of the literature on determinants of dental caries has been limited to socio-economic and behavioural aspects: we found few studies evaluating the effects of family environment and parental oral hygiene behaviour. Children belonging to lower socio-economic classes experienced more caries. In more than half the studies, children of highly educated, professional and high income parents were at lower risk for dental caries. There were conflicting results from studies on the effect of variables related to family environment, parents' oral hygiene behaviour and parent's disease status on dental caries in their children.